2018
DOI: 10.1016/j.chemosphere.2018.03.186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triclosan in breast milk on the infant fecal microbiome

Abstract: Triclosan is frequently used for its antimicrobial properties and has been detected in human serum, urine, and breast milk. Animal and molecular studies have shown that triclosan exerts a wide range of adverse health effects at both high (ppm) and low (ppb) concentrations. Since triclosan is of growing concern to human and environmental health, there is a need to improve extraction procedures and to study additional effects from triclosan exposure. In this study, we have improved triclosan extraction from brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 37 publications
(48 reference statements)
0
36
0
1
Order By: Relevance
“…We believe it unlikely that TCs would directly decrease infection rates by altering the babies' microbial flora. Although this possibility does exist [28], in adults, at much higher levels of exposure, TC-containing wash products have been found to have no effect on the microbiome of the gut or the mouth [29]. The use of TCs in household cleaning products, however, may have a substantial effect on environmental microbes, by decreasing their overall abundance and possibly restricting their variation [30].…”
Section: Discussionmentioning
confidence: 99%
“…We believe it unlikely that TCs would directly decrease infection rates by altering the babies' microbial flora. Although this possibility does exist [28], in adults, at much higher levels of exposure, TC-containing wash products have been found to have no effect on the microbiome of the gut or the mouth [29]. The use of TCs in household cleaning products, however, may have a substantial effect on environmental microbes, by decreasing their overall abundance and possibly restricting their variation [30].…”
Section: Discussionmentioning
confidence: 99%
“…They reported thatindependent of treatment -"infants with higher triclosan levels also showed an enrichment of Proteobacteria species." Bever et al [90] studied triclosan in breast milk in relation to personal care product use by mothers. They reported that "bacterial diversity in the fecal microbiome of the infants exposed to breast milk with detectable triclosan levels differed compared to their peers exposed to milk containing non-detectable amounts."…”
Section: Nexus: Environmental Chemicals Human Microbiome Health Riskmentioning
confidence: 99%
“…Triclosan is a broad-spectrum antimicrobial, present as one of the main components in many pharmaceuticals, personal care products, household products such as beddings, dish-washing products and sporting items from where it gets into the environment through wastewater (Dhillon et al 2015). Triclosan and its metabolites had been isolated in human fluids including breast milk (Bever et al 2018). Triclosan has been to shown to induce overall depression of the central nervous system in mice, decrease sperm count in male rats, and malformations in foetal development (James et al 2010;Dhillon et al 2015).…”
Section: Introductionmentioning
confidence: 99%